Top tips for a teaching fellowship. (December 2014) - Roberts, David; Morris, George; Crees, Amy; Slade, Timothy; Jakeman, Nicola
Summary Background Dedicated medical education posts are an exciting opportunity for doctors to focus on their development as clinical teachers. Within the seven hospital trusts that host students from the University of Bristol there are now 19 clinical teaching fellowship (CTF) posts. On starting a dedicated medical education post, the opportunities available can seem overwhelming, and on reflection many of the local 2012–13 CTFs would have changed their initial practice. The purpose of this article was to explore and collate the experiences of CTFs to produce a selection of practical 'top tips'. Methods A questionnaire was sent to all 19 CTFs via e–mail, asking them to state what they would do the same and what they would do differently if they had their time again. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Dedicated medical education posts are an exciting opportunity for doctors to focus on their development as clinical teachers </boxed-text> Results Eight themes were drawn from the 13 (68%) returned questionnaires, with each theme mentioned between four and 11 times. The themes included: keeping a portfolio of evidence; personal development; undertaking educational research; developing as a clinical teacher; and administration. Conclusion Our aim for this article was to generate practical top tips for those doctors considering, about to start or having just commenced a dedicated teaching role, helping individuals to get the most from their time. It also explains what these teaching fellowships can involve, and gives those thinking of undertaking a dedicated teaching role a better idea of what to expect.